Attributable Risk of Infection to mTOR Inhibitors Everolimus and Temsirolimus in the Treatment of Cancer. (25th November 2016) - Garcia, Christine A.; Wu, Shenhong
ABSTRACT: The risk of infection attributable to mTOR inhibitors has not been determined. Databases from PubMed and abstracts presented at the American Society of Clinical Oncology meetings were searched. Eligible studies included randomized controlled trials, in which everolimus or temsirolimus was compared with placebo. A total of 12 trials were included. The attributable incidences of all-grade and high-grade infections to mTOR inhibitors were 9.3% (95% confidence interval (CI): 5.8–14.6%) and 2.3% (95% CI: 1.2–4.4%) respectively. The risk varied widely with tumor types ( p <.001). There was substantial risk of infection attributable to mTOR inhibitors everolimus and temsirolimus.